A phenomenological approach to social entrepreneurship - Morúa, Juan; Agudelo Gutiérrez, David Steven; Méndez Valencia, Sergio (Cooperativismo & Desarrollo, 2022)
Social entrepreneurship allows different actors to interact in joint actions which allow improving the living conditions of society; in this interaction reflexive processes guided by dialogue arise; Thus, the purpose of this study is to offer a phenomenological proposal to be carried out within action intervention processes supported by systems theory with a constructivist and cognitivist vision. The method was based on the bibliographic review of the key concepts (social entrepreneurship and systems theory), to then study the case of a qualitative study with an ethnographic approach carried out with an ecotourism social enterprise. As a relevant result, the need to help social enterprises through action intervention processes is proposed, guided theoretically through the phenomena derived from systems theory, which allow them to understand and act in a way that is more in line with their nature as a project. Social.